2020
DOI: 10.1088/2515-7647/ab6742
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for photonic integrated circuits in optical gas sensors

Abstract: In this article, the potential of photonic integrated circuits (PICs) for modern gas sensing applications is discussed. Optical detection systems can be found at the high-end of the currently available gas detectors, and PIC-based optical spectroscopic devices promise a significant reduction in size and cost. The performance of such devices is reviewed here. This discussion is not limited to one semiconductor platform, but includes several available platforms operating from the visible wavelength range up to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 127 publications
0
35
0
Order By: Relevance
“…Given the completion of the integration on a chip of photonic sensors operating in UV-visible or near-IR [15], a miniaturization approach can also be seriously considered in mid-IR sensing. The development of a micro-sensor based on thin-film waveguide allows the miniaturization of the photonic device.…”
Section: Introductionmentioning
confidence: 99%
“…Given the completion of the integration on a chip of photonic sensors operating in UV-visible or near-IR [15], a miniaturization approach can also be seriously considered in mid-IR sensing. The development of a micro-sensor based on thin-film waveguide allows the miniaturization of the photonic device.…”
Section: Introductionmentioning
confidence: 99%
“…This has been driven partly by the opportunities for sensitive spectroscopic detection of trace chemicals [ 1 ], since in gas form the narrow mid-IR absorption lines that can positively identify a given chemical are 2–3 orders of magnitude stronger than those in the near IR. Applications include monitoring greenhouse gases [ 1 ], industrial process control [ 2 ], combustion diagnostics [ 3 ], clinical breath analysis [ 4 ], and isotope differentiation [ 5 ]. However, the long-term market for mid-IR chemical sensing products will depend in large part on such practical factors as cost, power budget, and system footprint.…”
Section: Introductionmentioning
confidence: 99%
“…However, the long-term market for mid-IR chemical sensing products will depend in large part on such practical factors as cost, power budget, and system footprint. While other sensing techniques, such as gas chromatography and monitoring variations in the properties of metal oxide semiconductors or polymers, may also be employed [ 6 ], laser spectroscopy combines the advantages of selectivity, sensitivity, stability, longevity, and range in the case of remote sensing [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination with HCFs allows for a sensing system with a small footprint, as HCFs allow for long propagation lengths while maintaining small size. Further size reductions can be achieved with a PIC-based gas interaction cell [7]. Tombez et al demonstrated a silicon photonics methane sensor employing an on-chip interaction cell [8].…”
Section: Introductionmentioning
confidence: 99%